Safe Transitions Pathway for Postcraniotomy Neurological Surgery Patients: High-Value Care That Bypasses the Intensive Care Unit. (1st September 2019) - Young, Jacob S; Chan, Andrew Kai-Hong; Viner, Jennifer; Sankaran, Sujatha; Chan, Alvin Y; Amara, Dominic; Magill, Stephen T; Osorio, Joseph A; Gibson, Lizbeth; Sanftner, Peter; Ward, Mariann; Ward, Tracy; et al.
Abstract: INTRODUCTION: High-value medical care is described as excellent outcomes, high patient satisfaction, and efficient costs. Neurosurgical care can be expensive for the hospital, as substantial costs are accrued during the operation and throughout the postoperative stay. At our institution, we implemented a "safe transitions pathway" where select patients would go to the transitional care unit (TCU) rather than the neuroscience intensive care unit (ICU) following a craniotomy. METHODS: Patients who were enrolled during the fiscal year (FY) 2018 were included in the study. The electronic medical record was reviewed for clinical information and the hospital bill was reviewed for financial information. Nurses and patients were given a satisfaction survey to assess their respective impression of the hospital stay and recovery pathway RESULTS: No patients who proceeded to the TCU post operatively were upgraded to ICU level of care overnight. There were no deaths in the STP patients and no patient required a return to the operating room during their hospitalization. There was a trend towards less 30-day readmissions in the STP patients than the standard pathway patients (1.2% vs 5.1%, P = .058). The mean number of ICU days saved per case was 1.20. The average post-procedure LOS was reduced by 0.25 d for STP patients. Actual FY18 direct cost savings from 94 patients who went through the Safe Transitions Pathway was 422 128. CONCLUSION: Length of stay, direct charges, total costs, and ICU days were significantly decreased while net revenue was significantly increased by the adoption of a STP. There were no substantial complications or adverse patient outcomes.